2004
DOI: 10.1103/physreve.69.066140
|View full text |Cite
|
Sign up to set email alerts
|

Absorbing state phase transitions with quenched disorder

Abstract: Quenched disorder -in the sense of the Harris criterion -is generally a relevant perturbation at an absorbing state phase transition point. Here using a strong disorder renormalization group framework and effective numerical methods we study the properties of random fixed points for systems in the directed percolation universality class. For strong enough disorder the critical behavior is found to be controlled by a strong disorder fixed point, which is isomorph with the fixed point of random quantum Ising sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
117
3
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(138 citation statements)
references
References 52 publications
17
117
3
1
Order By: Relevance
“…Its behavior close to the dirty critical point λ c can be obtained within the strong disorder renormalization group method [31,36,38]. When approaching the phase transition, z ′ diverges as…”
Section: Griffiths Singularitiesmentioning
confidence: 97%
“…Its behavior close to the dirty critical point λ c can be obtained within the strong disorder renormalization group method [31,36,38]. When approaching the phase transition, z ′ diverges as…”
Section: Griffiths Singularitiesmentioning
confidence: 97%
“…An RG study by (Hooyberghs et al, 2002) showed that in case of strong enough disorder the critical behavior is controlled by an infinite randomness fixed point (IRFP), the static exponents of which in 1d are…”
Section: Quench Disordered Dp Systemsmentioning
confidence: 99%
“…(16,19), the exponent x ′ has then been calculated from The ratio of exponents η/δ measured in Monte Carlo simulations for different values of β. The value at β = 0 is the SDRG prediction for the one-dimensional random contact process [23].…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%